Low temperature sputtered TiO2 nano sheaths on electrospun PES fibers as high porosity photoactive material1. Issue 90 (1st October 2015) - Alberti, A.; Bongiorno, C.; Pellegrino, G.; Sanzaro, S.; Smecca, E.; Condorelli, G. G.; Giuffrida, A. E.; Cicala, G.; Latteri, A.; Ognibene, G.; Cassano, A.; Figoli, A.; et al.
<x xml:space="preserve">Abstract</x> Low temperature approach based on combining electrospinning and reactive sputtering processes to realise a porous mesh of PES fibers wrapped by TiO2 nano-sheaths, active under UV illumination.